2023
DOI: 10.3390/ijerph20032484
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Pediatric Pain in Spain: A Survey Study

Abstract: Pain is a common experience among children and adolescents, and pain management in this population is a challenge to clinicians. The aims of this study were to increase our understanding of current practices in the management of both acute and chronic pediatric pain in Spain, explore potential barriers to ideal practices, and identify professional needs as perceived by healthcare professionals. A total of 277 healthcare professionals took part, all of whom had wide experience in managing children and adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…We believe that the lack of training or information on multimodal analgesia methods among most participants, along with the anesthesiologists' tendency to primarily use IV drugs for postoperative pain management, may have contributed to this result. Similarly, Miró et al [18] have suggested that limited access to sufficient education and training is one of the main obstacles to proper pain management by healthcare professionals in pediatric cases.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the lack of training or information on multimodal analgesia methods among most participants, along with the anesthesiologists' tendency to primarily use IV drugs for postoperative pain management, may have contributed to this result. Similarly, Miró et al [18] have suggested that limited access to sufficient education and training is one of the main obstacles to proper pain management by healthcare professionals in pediatric cases.…”
Section: Discussionmentioning
confidence: 99%
“…Parents are requesting interventions other than pharmacological as many children take numerous medications which are often limited by adverse side effects [ 21 ]. Clinicians have reported key barriers to effective pain management including a lack of access to some interdisciplinary team members and inadequate pain education for health professionals and children and families [ 66 , 67 ].…”
Section: Management Of Pain In Children and Young People With Cpmentioning
confidence: 99%